The Use of Audio-Visual Media to Improve Learning Outcomes in Social Studies (IPAS) for Third Grade Students of SD Negeri 07 Kinali - Oktira, Yona Syaida; Agustin , Moni Silfi; Efrina, Gusnita; Stavinibelia, Stavinibelia; Efendi, Nofriza (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The background to the problem in this research is low student learning outcomes, school facilities and infrastructure are incomplete and teachers rarely use media during learning. This research aims to improve the science and science learning aoutcomes of class III students at SD Negeri 07 Kinali. This research was conducted from October to December 2023. In the independent curriculum, science and social studies subjects are combined into one called IPAS. Natural and social science or (IPAS) is a science that discusses living things and inanimate objects and discusses human life as individual and social creatures. The method used in this research is classroom action research (PTK). This research used 2 cycles consisting of four interrelated stages. The four stages are the planning stage, implementation stage, observation and reflection stage. The results of this research show that the use of audio visual media can improve sciencelearning outcomes for class III students at SD Negeri 07 kinali. Students become more motivated and active in the teaching and learning process. In cycle I, student learning outcomes were 63,25%, while in cycle II it reached 86%, this increase in scores proves that there has been an increase in student learning outcomes through audio visual media at SD N egeri 07 kinali.